Successful Treatment of Cryotherapy Resistant Verruca Vulgaris with 18% Aluminum Chloride Solution: A Report of 4 Cases - Kübra Pınar Hararcı Yıldırım; Sabir Hasanbeyzade; Efsun Tanaçan; Didem Dinçer Rota (Indian Dermatology Online Journal)
Warts are benign intraepidermal proliferations commonly seen in children and adults caused by Papillomavirus. Invasive and non-invasive methods such as salicylic acid, cryotherapy, imiquimod, intralesional 5-fluorouracil, and electrocauterization take part in the treatment. In this study, we present 4 cryotherapy-resistant verruca cases treated successfully with 18% aluminum chloride solution. It is thought that the aluminum chloride solution acts by desquamation of the epidermis with its intraepidermal keratinolytic effect in the virus-infected epidermis. As a result of treatment, clinical improvement was seen in all cases. This treatment option can be used because it is painless, leaves no scarring, the frequency of hospital admission is low and the results are fast.